2021
DOI: 10.21037/atm-21-5767
|View full text |Cite
|
Sign up to set email alerts
|

Y-box binding protein 1 regulates liver lipid metabolism by regulating the Wnt/β-catenin signaling pathway

Abstract: Background: We mainly investigated how y-box binding protein 1 (YB-1) regulates liver lipid metabolism through the Wnt/β-catenin signaling pathway using multiple models.Methods: The LO2 cells were treated with palmitic acid (PA) to create an NAFLD model in vitro.Immunohistochemistry and Western blotting assays were used to detect the expression of YB-1, β-Catenin, SREBP-1c, LXRa, FXR1 and PPARα protein, and RNAs of them was detected by qRT-PCR. Oil Red O assay was applied to observe lipid droplets in LO2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, the role of ILF2 in the regulation of lipid metabolism/NAFLD has not been reported. A recent study has demonstrated that YB-1, a ILF2 interacting protein, regulates liver lipid metabolism by regulating the Wnt/β-catenin signaling pathway 49 , which implied the possibility of ILF2 in the regulation of NAFLD. Thus, this study reports that ILF2 is a potential positive modulator of lipid metabolism by inhibiting fatty acid biosynthesis genes expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of ILF2 in the regulation of lipid metabolism/NAFLD has not been reported. A recent study has demonstrated that YB-1, a ILF2 interacting protein, regulates liver lipid metabolism by regulating the Wnt/β-catenin signaling pathway 49 , which implied the possibility of ILF2 in the regulation of NAFLD. Thus, this study reports that ILF2 is a potential positive modulator of lipid metabolism by inhibiting fatty acid biosynthesis genes expression.…”
Section: Discussionmentioning
confidence: 99%
“…6 YBX-1 regulates gene transcription by binding to promoters with Y-box motifs. 7 Previous studies have found that YBX-1 is involved in tumor regulation. For example, overexpression of YBX-1 can promote the growth of pancreatic ductal adenocarcinoma and inhibit cell apoptosis by up-regulating of GSK3β axis.…”
Section: Introductionmentioning
confidence: 99%